What have we learned from cancer immunotherapy in the last 3 years? - Ascierto, Paolo A (BioMed Central, 2014)
Until recently, most immunotherapeutic approaches used to fight cancer were ineffective, counteracted by the tumour’s ability to evade immune attack. However, extensive research has improved our understanding of tumour immunology and enabled the development of novel treatments that can harness the patient’s immune system and prevent immune escape. Over the last few years, through numerous clinical trials and real-world experience, we have accumulated a large amount of evidence regarding the potential for long-term survival with immunotherapy agents in various types of malignancy. The results of these studies have also highlighted a number of recurring observations with immuno-oncology agents, including their potential for clinical application across a broad patient population and for both conventional and unconventional response patterns. Furthermore, given the numerous immune checkpoints that exist and the multiple mechanisms used by tumours to escape the immune system, targeting distinct checkpoint pathways using combination approaches is an attractive therapeutic strategy with the potential to further enhance the antitumour immune response.